Product indiscriminate use of vitamin risks: A review. Issue 12 (3rd July 2020) - Mello, Acsa Lima Marinho Fonseca de; Melo, Karolynne Rodrigues de; Sousa, André Luiz Moreira Domingues de; Rolim Neto, Pedro José; Silva, Rosali Maria Ferreira da
Abstract: Most of the population does not seek professional advice before taking vitamin products and their indiscriminate use can lead to serious health risks. This study aims to demonstrate, through bibliographic survey, the risks of indiscriminate use of vitamin products related to hypervitaminosis and major drug interactions which the multivitamins are involved. A bibliographic survey was conducted in the databases LILACS, SciELO, PubMed, Medline, Micromedex, Drugs.com and textbooks on the subject. Vitamins are commonly described as harmless products by the majority of the population, but these trace elements can interact with other substances, causing mild disconforts or treatment failure for the patient, severe consequences to the body and can lead to death. To avoid the indiscriminate use of vitamin products, it is necessary that health professionals know and use specific laboratory tests for the determination of vitamins in the body, preventing these products from being unnecesarily prescribed. Also, the knowledge about what the possible effects of the indiscriminate use of vitamin supplements can lead to the rational use of these products.